2006
DOI: 10.1093/jn/136.10.2653
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model Gives Insights into Nutritional and Genetic Aspects of Folate-Mediated One-Carbon Metabolism

Abstract: Impaired folate-mediated 1-carbon metabolism has been linked to multiple disease outcomes. A better understanding of the nutritional and genetic influences on this complex biochemical pathway is needed to comprehend their impact on human health. To this end, we created a mathematical model of folate-mediated 1-carbon metabolism. The model uses published data on folate enzyme kinetics and regulatory mechanisms to simulate the impact of genetic and nutritional variation on critical aspects of the pathway. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
131
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 75 publications
5
131
0
3
Order By: Relevance
“…2), in which metabolites activate or inhibit enzymes in the network. Our analysis has shown that these regulatory interactions serve to stabilize a few specific reactions in the system, namely: the TS reaction which is the rate-limiting step for DNA synthesis, the AICART reaction which is an early step in the de novo synthesis of nucleotides, the DNMT reaction which ensures correct methylation of newly replicated DNA, and also the synthesis of glutathione (not shown) (Nijhout et al 2004(Nijhout et al , 2006bReed et al 2006Reed et al , 2008. As amino acid input into the system varies, for instance with meals, these homeostatic mechanisms maintain stability of these critical reactions.…”
Section: Robustness and Cryptic Genetic Variationmentioning
confidence: 90%
“…2), in which metabolites activate or inhibit enzymes in the network. Our analysis has shown that these regulatory interactions serve to stabilize a few specific reactions in the system, namely: the TS reaction which is the rate-limiting step for DNA synthesis, the AICART reaction which is an early step in the de novo synthesis of nucleotides, the DNMT reaction which ensures correct methylation of newly replicated DNA, and also the synthesis of glutathione (not shown) (Nijhout et al 2004(Nijhout et al , 2006bReed et al 2006Reed et al , 2008. As amino acid input into the system varies, for instance with meals, these homeostatic mechanisms maintain stability of these critical reactions.…”
Section: Robustness and Cryptic Genetic Variationmentioning
confidence: 90%
“…We observed that the degree or the pattern of global DNA methylation in tissues of the cervix is not altered by the fortification (1). A recently described mathematical simulation of folate-mediated 1-carbon metabolism (2) reported that intracellular methionine concentrations are relatively insensitive to variation in total folate, but intracellular concentration of S-adenosyl-methionine (SAM) had a strong linear association with total folate concentration suggesting that SAM concentrations are likely to be elevated due to higher folate intake as a result of the folic acid fortification. Even a short term supplementation with folic acid (1.2 mg/day for 12 week) has been shown to increase whole blood SAM in humans (3).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic labeling studies, in vitro binding experiments, and mathematical modeling have indicated that methylene-THF is preferentially directed toward methionine synthesis relative to thymi-* This work was supported by Public Health Service Grant DK58144. The costs dylate biosynthesis (13,14). There is increasing evidence that the partitioning of methylene-THF between methionine and thymidylate synthesis is central to the origin of folate-related pathologies.…”
mentioning
confidence: 99%